2015
DOI: 10.4134/jkms.2015.52.3.489
|View full text |Cite
|
Sign up to set email alerts
|

Duo Ring Property Restricted to Groups of Units

Abstract: Abstract. We study the structure of right duo ring property when it is restricted within the group of units, and introduce the concept of right unit-duo. This newly introduced property is first observed to be not left-right symmetric, and we examine several conditions to ensure the symmetry. Right unit-duo rings are next proved to be Abelian, by help of which the class of noncommutative right unit-duo rings of minimal order is completely determined up to isomorphism. We also investigate some properties of righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Following Han et al [14], a ring is called right unit-duo if [a] ℓ ⊆ [a] r for every a ∈ R. Left unit-duo rings are defined similarly. A ring is unit-duo if it is both We consider next the right unit-duo ring property on the powers of elements.…”
Section: [X] (R[[x]])mentioning
confidence: 99%
See 2 more Smart Citations
“…Following Han et al [14], a ring is called right unit-duo if [a] ℓ ⊆ [a] r for every a ∈ R. Left unit-duo rings are defined similarly. A ring is unit-duo if it is both We consider next the right unit-duo ring property on the powers of elements.…”
Section: [X] (R[[x]])mentioning
confidence: 99%
“…for all a i ∈ K and g i ∈ G. We have also that KG is left unit-duo if and only if it is right unit-duo by [14,Theorem 1.3(4)]. Recall that Q 8 denotes the quaternion group.…”
Section: [X] (R[[x]])mentioning
confidence: 99%
See 1 more Smart Citation
“…In [8], it was shown that any right (left) unit-duo ring R is abelian (i.e., every idempotent in R is central). In [11], it was also shown that if a ring R has a finite number of equivalence classes under ≃ ℓ , then R is an artinian ring with J(R) n+1 = 0 where n is the number of classes under ≃ ℓ .…”
Section: Properties Of Unit-duo Ringsmentioning
confidence: 99%
“…∼ r ). A ring R is called unit-duo if [x] ℓ = [x] r for all x ∈ R (refer [8]). Any commutative ring and a finite direct product of division rings are unit-duo rings.…”
Section: R[x]mentioning
confidence: 99%